Patient outcomes in Tropical North Queensland after implementation of a dedicated orthopaedic trauma list. Issue 5 (6th April 2021) - Knight, Matthew; Gouk, Conor; Jorgensen, Nicholas B.; Puri, Arvind; Morrey, Christopher
Abstract: Background: To assess patient outcomes after the introduction of a regular orthopaedic‐specific trauma list (OTL). Methods: A retrospective analysis of 422 trauma cases was performed comparing patient outcomes after the introduction of the OTL. Four common traumatic injuries requiring operative intervention were considered; closed tibial fractures, intra‐capsular neck of femur fractures, displaced paediatric supracondylar humeral fractures and hand tendon injuries. The outcomes assessed included time from patient referral to theatre, time from admission to theatre, operative times, time of day operation commenced, consultant involvement, hospital length of stay (LOS), returns to theatre and mortality. Results: Tibial fractures had an increased time from admission to theatre (0.46 days pre‐OTL versus 1.21 days post‐OTL, P  = 0.01), hand tendons injuries had an increase in time from referral to theatre (1.06 days pre‐OTL versus 2.82 days post‐OTL, P  = 0.001). Consultant involvement increased for supracondylar procedures (27% pre‐OTL versus 61% post‐OTL, P  < 0.001) and tendinous hand injury repairs (5% pre‐OTL versus 37% post‐OTL, P  < 0.001). There was a decrease in cases starting after 17:00 hours; however, no group reached statistical significance. There was a reduction in complications and shorter inpatient LOS, however; these were not statistically significant. There was no difference in overall operative times after OTL implementation; however, individual group differences existed between registrars and consultants. Conclusion: Implementing regular orthopaedic trauma lists resulted in greater consultant involvement and was associated with decreased after‐hours operating. Delays to theatre increased from both time of referral and admission; however, this was not correlated with increases in significant harm. Abstract : Assessing outcomes for trauma patients after implementation of a dedicated orthopaedic trauma list.